Vibrio diversity and dynamics in the Monterey Bay upwelling region - Mansergh, Sarah; Zehr, Jonathan (Frontiers in Microbiology, 2014)
The Vibrionaceae (Vibrio) are a ubiquitous group of metabolically flexible marine bacteria that play important roles in biogeochemical cycling in the ocean. Despite this versatility, little is known about Vibrio diversity and abundances in upwelling regions. The seasonal dynamics of Vibrio populations was examined by analysis of 16S rRNA genes in Monterey Bay (MB), California from April 2006-April 2008 at two long term monitoring stations, C1 and M2. Vibrio phylotypes within MB were diverse, with subpopulations clustering with several different cultured representatives including Allivibrio spp., Vibrio penaecida and Vibrio splendidus as well as with many unidentified marine environmental bacterial 16S rRNA gene sequences. Total Vibrio population abundances, as well as abundances of a Vibrio sp. (MBAY Vib7) subpopulation and an Allivibrio sp. (MBAY Vib4) subpopulation were examined in the context of environmental parameters from mooring station and CTD cast data. Total Vibrio populations showed some seasonal variability but greater variability was observed within the two subpopulations. MBAY Vib4 was negatively associated with MB upwelling indices and positively correlated with oceanic season conditions, when upwelling winds relax and warmer surface waters are present in MB. MBAY Vib7 was also negatively associated with upwelling indices and represented a deeper Vibrio sp. population. Correlation patterns suggest that larger oceanographic conditions affect the dynamics of the populations in MB, rather than specific environmental factors. This study is the first to target and describe the diversity and dynamics of these natural populations in MB and demonstrates that these populations shift seasonally within the region.